A Case of Esophageal Crohn’s Disease Resistant to Corticosteroids but Responsive to Cyclosporine A - PL Beck; TE Lay (Canadian Journal of Gastroenterology)
Esophageal ulceration is a rare and potentially devastating complication of Crohn’s disease (CD). A 29-year-old male with odynophagia is described. He had no prior history of inflammatory bowel disease, connective tissue disorder or rheumatological disease. He denied symptoms of a recent viral infection and did not have significant human immunodeficiency virus risk factors. He did not have eye, skin, oral or genital lesions. Omeprazole failed to control his symptoms. On endoscopy, large esophageal ulcerations were noted. Biopsies showed active chronic inflammation with granulomatoid changes. Autoimmune, viral and acid-fast bacilli studies were normal. The odynophagia failed to improve, and he subsequently developed right lower quadrant pain and hematochezia. Colonoscopy demonstrated extensive hemorrhagic ileal ulcers, and biopsies were suggestive of CD. The odynophagia did not respond to high dose intravenous steroids and bowel rest. The patient was reluctant to take cytotoxic agents, and thus a course of cyclosporine A was initiated. The patient responded rapidly and was able to tolerate a full diet within 48 h. Repeat gastroscopy was normal. To the authors’ knowledge, this is the first reported case of esophageal CD treated with cyclosporine A.